Establishment of human Leber’s hereditary optic neuropathy model using iPSC-derived retinal organoids - Aoshima, Kota; Takagi, Yuya; Funato, Michinori; Kuse, Yoshiki; Nakamura, Shinsuke; Shimazawa, Masamitsu (Frontiers in Cellular Neuroscience, 2025)
Leber’s hereditary optic neuropathy (LHON) is a mitochondrial disease caused by mitochondrial DNA mutations, leading to central vision loss and retinal ganglion cell (RGC) degeneration. Progress in understanding LHON and developing treatments has been limited by the lack of human-like models. In this study, we aimed to establish a human retinal model of LHON using retinal organoids (ROs) from LHON patient-derived induced pluripotent stem cells (LHON-iPSCs). We first confirmed LHON-iPSCs were successfully differentiated into ROs (LHON-ROs). LHON-RO showed a reduction in RGC numbers and the density of neural axons. Additionally, both mitochondrial membrane potential and ATP production were decreased in LHON-RO. Finally, treatment with idebenone, the only approved therapeutic agent for LHON, improved RGC numbers in LHON-RO. This model replicates key clinical features of LHON, including RGC and axonal loss, and demonstrates idebenone’s therapeutic potential. Furthermore, a comprehensive analysis of the LHON-RO model revealed impaired mitophagy, suggesting novel therapeutic targets for LHON. Thus, the LHON-RO model offers a valuable platform for studying LHON pathogenesis and evaluating treatments.